2019
DOI: 10.1155/2019/5237642
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of Oral Vitamin D2 Supplementation on Psoriasis: A Double-Blind, Randomized, Placebo-Controlled Study

Abstract: Background. There are limited randomized controlled trials of oral vitamin D supplementation in psoriasis, especially in Asia, and the results are inconclusive. Objective. To investigate the clinical effect of oral vitamin D supplementation on psoriasis. Methods. Patients with psoriasis were randomized to receive vitamin D2 60,000 IU or similar-looking placebo pills once every 2 weeks for 6 months. The primary outcome was improvement of the Psoriasis Area and Severity Index (PASI) score at 3 and 6 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 33 publications
(36 reference statements)
2
23
3
4
Order By: Relevance
“…32 Similar results were obtained in the randomised, double-blind, placebo-controlled study conducted by Disphanura et al, however, the treatment period was the same, but the vitamin D supplementation was intermittent every two weeks. 33 In contrast to the results presented in this paper, Jarrett et al found that oral vitamin D administration had no significant difference in the PASI score in patients with mild form of the disease. 34 The current study indicated the existence of a significant, but weak correlation between clinical improvements determined by change in PASI score and changes in TC and LDL-C serum level.…”
Section: Discussioncontrasting
confidence: 99%
“…32 Similar results were obtained in the randomised, double-blind, placebo-controlled study conducted by Disphanura et al, however, the treatment period was the same, but the vitamin D supplementation was intermittent every two weeks. 33 In contrast to the results presented in this paper, Jarrett et al found that oral vitamin D administration had no significant difference in the PASI score in patients with mild form of the disease. 34 The current study indicated the existence of a significant, but weak correlation between clinical improvements determined by change in PASI score and changes in TC and LDL-C serum level.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple clinical trials have attempted to investigate the influence of different forms of vitamin D supplementation on treatment of psoriasis, yielding varying results. A six-month study of psoriasis patients who received 60,000 IUs of vitamin D 2 once every 2 weeks not only showed significant improvement in their PASI (psoriasis area and severity index) score but also demonstrated a direct association with improvement in blood levels of 25(OH)D [ 84 ]. Another pilot study giving daily 35,000 IUs of vitamin D 3 to 9 patients with psoriasis and 16 patients with vitiligo who were vitamin D-deficient or insufficient for six months demonstrated a significant improvement in psoriasis area and severity index (PASI) in all psoriatic patients and 25–75% repigmentation in 14 of 16 vitiligo patients, without development of any complications suggestive of vitamin D toxicity including hypercalcemia, kidney stones, nephrocalcinosis, or hypercalciuria [ 85 ].…”
Section: Vitamin D and Immune-related Diseasesmentioning
confidence: 99%
“…The changes in serum concentrations of vitamin D metabolite 25(OH)D were used to monitor the side effects and were not related to the degree of improvement or worsening in psoriasis lesions. A vitamin D 2 dose higher than 40,000 IU was associated with hypercalcemia toxicity [ 40 ].…”
Section: Resultsmentioning
confidence: 99%